2018
DOI: 10.1016/j.echo.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Validation of the Echocardiographic Assessment of Left Ventricular Filling Pressures Using the 2016 Diastolic Guidelines: Head-to-Head Comparison with the 2009 Guidelines

Abstract: Background Recent American Society of Echocardiography (ASE)/European Association of Cardiovascular Imaging (EACVI) guidelines for echocardiographic evaluation of left ventricular (LV) diastolic function provide a practical, simplified diagnostic algorithm for estimating LV filling pressure. The aim of this study was to test the accuracy of this algorithm against invasively measured pressures and compare it with the accuracy of the previous 2009 guidelines in the same patient cohort. Methods Ninety patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 12 publications
4
92
3
4
Order By: Relevance
“…This is significantly lower than in our population where 21% of patients had indeterminate results with the ASE/EACVI algorithm. The discrepancy between our findings and those obtained by Balaney and colleagues (9) may be attributed to their sample selection as they only included patients undergoing left heart catheterisation whereas our study involved unselected patients attending for transthoracic echocardiography. In addition our study did not set out to evaluate the accuracy of the ASE/EACVI guidelines for assessing LV filling pressure, rather our aim was simply to determine the outcome of the application of the guideline in the clinical setting.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This is significantly lower than in our population where 21% of patients had indeterminate results with the ASE/EACVI algorithm. The discrepancy between our findings and those obtained by Balaney and colleagues (9) may be attributed to their sample selection as they only included patients undergoing left heart catheterisation whereas our study involved unselected patients attending for transthoracic echocardiography. In addition our study did not set out to evaluate the accuracy of the ASE/EACVI guidelines for assessing LV filling pressure, rather our aim was simply to determine the outcome of the application of the guideline in the clinical setting.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition our study did not set out to evaluate the accuracy of the ASE/EACVI guidelines for assessing LV filling pressure, rather our aim was simply to determine the outcome of the application of the guideline in the clinical setting. Balaney and colleagues (9) concluded that the main cause of an indeterminate grading within their study was attributed to insufficient TR to allow assessment of TR Vmax. This finding was also observed in our analysis as 68.2% of patients labelled with an indeterminate grading had no measurable TR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the LVEF, a combination of variables (at least 50% to 100% of these) may aid in the diagnosis of LV diastolic dysfunction with or without elevated LA pressure. However, invasive validation of diastolic measures has shown to have only a modest correlation with the 2009 as well as the 2016 ASE recommendations for LV diastolic function evaluation in preserved as well as reduced LVEF . The same group has shown that LA strain may be a superior marker that could not only discriminate all grades of LV diastolic dysfunction vs. normal with excellent areas under the curves but also demonstrate that LA strain is useful for “accurate characterization” of LV diastolic dysfunction .…”
Section: Could Biatrial and Rv Strain Aid In The Diagnosis Of LV Diasmentioning
confidence: 99%
“…Even though the framework of the 2009DF recommendations was built on the seminal study by Appleton et al 13 and the Mayo Clinic model, 14 the variables and cutoffs were not derived from these studies, and the classification system was validated post hoc. (c) The 2016DF classification has by now been validated against invasive measures 15–18 and showed good inter‐observer agreement irrespective of experience 4 …”
mentioning
confidence: 99%